PENGARUH KEJELASAN SASARAN ANGGARAN, PERENCANAAN ANGGARAN, DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA (STUDI EMPIRIS PADA ORGANISASI PERANGKAT DAERAH KOTA PEKANBARU) - Yolanda Rahmadhani; Muhammad Ahyaruddin; Siti Samsiah (SINERGI : Jurnal Riset Ilmiah, 2024)
This study aims to determine the effect of budget target clarity, budget planning, and reporting systems on performance accountability (empirical study on Regional Apparatus Organizations in Pekanbaru City). This type of research is quantitative research. This research was conducted at Regional Apparatus Organizations (OPD) in Pekanbaru City. The research was conducted from July to August 2024. The population in this study were all employees at the Pekanbaru City OPD totaling 1,354 people. The sampling technique used in this study was purposive sampling and a sample of 47 respondents was obtained. Data sources were primary data sources from questionnaires and secondary data sources from books and journals. The data collection technique used a questionnaire. Data analysis used multiple linear regression analysis methods with performance accountability as the dependent variable and three independent variables of budget target clarity, budget planning, and reporting systems. The results of this study state that the budget target clarity variable has a positive effect on performance accountability. Budget planning has a positive effect on performance accountability. The reporting system has a positive effect on performance accountability.